Symbol Determination Difficulties and the Interpretation of Symbol in Ancient Philosophy - Aleksanyan, Lilit (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
The symbol has a dual nature: it represents some idea by a material substrate. And traditionally philosophers have emphasized that feature of the symbol. In this sense, the symbol stands as the closest concept with the sign and image. But the image is too generalized. For the sign, the most important thing is its feature of pointing out. The symbol has a difficult and complex structure than the sign, and the symbol is the result of a more complex abstraction. When we say A is the sign of B, it means that A points out B, and when we say that A is the symbol B", here it is already necessary to bear in mind that A is the result of our understanding of B concentrated in A.
Keywords: symbol, culture, image, eidos, model, mystics, sign